LncRNA ZFHX4-AS1 initiates an oncogenic axis involving a ZFHX4/SOX2 positive feedback loop to accelerate glioma progression - Yan, Hongshan; Wang, Xue; Zhao, Zongmao (Frontiers in Oncology, 2025)
IntroductionThe long non-coding RNA ZFHX4-AS1 is a recently identified transcript with an unknown role in glioma. Here, we demonstrate that ZFHX4-AS1 and its neighboring protein-coding gene, ZFHX4, are both significantly upregulated in glioma, and their high expression correlates with poor patient prognosis.MethodsWe integrated pan-cancer and glioma transcriptomic datasets from TCGA to assess ZFHX4-AS1 and ZFHX4 expression patterns and their prognostic relevance. We analyzed the expression of ZFHX4-AS1 and its neighboring gene ZFHX4 in human glioma tissues and correlated it with patient prognosis. Functional assays, including cell proliferation, migration, and invasion tests, were conducted in vitro, and tumor growth was assessed in vivo. Additional mechanistic assays—including RNA-FISH, subcellular fractionation, and co-immunoprecipitation—were performed to determine the localization and molecular interactions of ZFHX4-AS1. The mechanistic interactions between ZFHX4-AS1, ZFHX4, SOX2, and the JAK-STAT pathway were investigated using gene expression analysis, protein-protein interaction studies, and signaling pathway activation assays.ResultsFunctionally, both ZFHX4-AS1 and ZFHX4 promote glioma cell proliferation, migration, and invasion in vitro and tumor growth in vivo. Mechanistically, ZFHX4-AS1 acts in cis to positively regulate the expression of ZFHX4. Crucially, we identified the stemness factor SOX2 as a key functional partner of ZFHX4. ZFHX4 and SOX2 physically interact and form a positive feedback loop, where each protein promotes the other’s expression. This regulatory circuit serves to amplify the oncogenic signal, robustly driving the malignant phenotype. Finally, we demonstrate that this signaling axis converges on the activation of the JAK-STAT pathway.DiscussionIn conclusion, our study significantly expands upon the understanding of the ZFHX4-AS1 pathway in glioma. We demonstrate that ZFHX4-AS1 initiates an oncogenic signal which is powerfully amplified by a previously unidentified ZFHX4/SOX2 positive feedback loop. We further establish that this entire axis ultimately converges on the activation of the JAK-STAT pathway. This detailed ZFHX4-AS1/ZFHX4/SOX2/JAK-STAT axis represents a promising set of therapeutic targets for glioma treatment.